(untitled) (Journal of Economic Research & Business Administration, 2016)
subject of attention of an extensive circle of participants of the market relations interested in results of its functioning. Practically all users of financial statements use methods of the financial analysis for decision-making on optimization of the interests. Heads and the relevant services, and also founders for the purpose of studying of effective use of resources, increase of profitability of the capital, ensuring stability of position of the enterprise are engaged in the analysis of a financial condition of the enterprise, organization. Owners analyze the reporting for increase of profitability of the capital, ensuring stability of position of the enterprise. Creditors and investors analyze financial reports to minimize the risks on loans and deposits, suppliers - for timely receiving payments, the tax inspections - for implementation of the plan of receipt of funds in the budget etc. It is possible to say firmly that quality of the made decisions entirely depends on quality of their analytical validity.